Литература русского зарубежья в польских учебных пособиях - Mianowska, Joanna (Acta Polono-Ruthenica, 2006)
This paper is a short history of presentation of Russian emigrant literature in Polish textbookssince the 1970s. The author emphasizes that even in the period of Marxist views the best specialistson the subject tried to overcome the pressure of the dominant ideology and to give a completethough necessarily brief analysis of the most important writers of the „first wave” of Russianemigration. In the 1990s starts the process of „rediscovery” of many unknown names in the „thirdwave” of Russian emigrant literature which have also found their way into the textbooks. Theauthor believes that the ever increasing development of scientific research in the field will result inthe appearance of a new Polish textbook which will be able to fully satisfy the students’ needs.